CHARACTER EDUCATION STRATEGY OF KYAI HASAN GENGGONG IN THE BOOK "150 YEARS OF SPREADING KNOWLEDGE IN THE WAY OF ALLAH" - Sholeh, Adam Wildan (Edumanajerial : Journal of Educational Management, 2024)
This study discusses the values of character education which are important points as a support for education in Indonesia and the general public. As the development of the world is increasingly advanced, this also results in a decrease in the quality of students in terms of morals and manners. The object of this research is an ancient book published in 1975 entitled (150 years of spreading knowledge in the way of Allah) which contains the history of the development of a religious scholar named Kyai Hasan Genggong, he was a charismatic figure in his time who gave birth to many scholars and influential figures in Indonesia, so that the formulation of the problem is what are the values and implementation of character education built by Kyai Hasan in educating the nation's children? The theoretical study used was a guideline for the implementation of character education by the ministry of national education in 2011. This research is a library research using a qualitative descriptive approach. The results obtained show that there are four values of character education including: (a). Learning planning, (b). Development and integration, (c). Implementation in society, (d). Evaluation and control.